Turning the Tide on Hepatitis Delta in Pakistan: An Urgent Call for Awareness, Access, and Action. - Saeed Sadiq Hamid; Syed Munawar Ali; Zaigham Abbas; Ghias Un Nabi Tayyab; Rao Saad Ali Khan; Asher Bin Feroze; Saad Khalid Niaz (International Journal of Endorsing Health Science Research, 2025)
Background: Hepatitis Delta Virus (HDV) remains an under-recognized contributor to advanced liver disease in Pakistan despite the country’s high burden of Hepatitis B Virus (HBV). Fragmented screening practices, inconsistent confirmatory testing, and absence of standardized national protocols limit effective disease control. Methodology: This short communication synthesizes previously published clinician-perspective data from major tertiary centers in Pakistan alongside international HDV guidelines and regulatory frameworks. The aim is to identify structural gaps and propose a standardized national response model. Results: Available data suggest that HDV co-infection among HBV patients in Pakistan is substantial, with diagnostic access constrained primarily by affordability and inconsistent RNA confirmation capacity. The absence of unified screening algorithms and dedicated programmatic inclusion has resulted in delayed detection and limited therapeutic access. Broad expert agreement supports integration of HDV into national hepatitis strategies and development of regulated early-access pathways for emerging therapies. Conclusion: The cumulative evidence supports the hypothesis that HDV constitutes a significant but structurally neglected public health burden in Pakistan. Establishing standardized screening protocols, improving diagnostic affordability, and incorporating HDV into national hepatitis policy frameworks are essential to reduce preventable liver-related morbidity and mortality.